1997
DOI: 10.1897/1551-5028(1997)016<2222:pbcaso>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Polychlorinated Biphenyl Congeners and Selected Organochlorines in Lake Superior Fish, Usa

Abstract: Abstract-Walleye, whitefish and whitefish livers, lake trout, and siscowet lake trout were collected from the Apostle Islands Region of Lake Superior. Carp were obtained from a Lake Michigan tributary near Oshkosh, Wisconsin, USA. Each fish species was analyzed for 89 polychlorinated biphenyl congeners, 12 selected organochlorines, and total lipids. Congener profiles varied greatly between the fish species. Carp and whitefish contained tri-and tetra-chlorobiphenyl congeners, such as 28ϩ31, 63, and 66ϩ95 in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1998
1998
2002
2002

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Other research has shown that this pattern of coplanar PCB concentration occurs in a wide variety of species such as lake trout from Lake Michigan, killer whale, and Baltic herring (summarized in Patterson et al, 1994). Gerstenberger et al (1997) analyzed PCB congeners in Lake Superior walleye, pink salmon, siscowet trout, carp, and whitefish. The PCB congener pattern in walleye and siscowet was similar to the chinook salmon from the current study with congeners 138 and 153 predominating.…”
Section: Resultsmentioning
confidence: 99%
“…Other research has shown that this pattern of coplanar PCB concentration occurs in a wide variety of species such as lake trout from Lake Michigan, killer whale, and Baltic herring (summarized in Patterson et al, 1994). Gerstenberger et al (1997) analyzed PCB congeners in Lake Superior walleye, pink salmon, siscowet trout, carp, and whitefish. The PCB congener pattern in walleye and siscowet was similar to the chinook salmon from the current study with congeners 138 and 153 predominating.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, there are profound differences among taxa with respect to the uptake and metabolism of PCB congeners. Carp (especially) accumulate lower-chlorinated congeners that may exhibit thyroid-, neuro-, or endocrine-mediated toxicity (Gerstenberger et al 1997). Therefore, the ecological risk represented by PCB residues in the 1995 fish samples is unknown.…”
Section: Pcbsmentioning
confidence: 99%
“…bAbreviated structures in format commonly presented. Tables 8 and 9 and references (146)(147)(148)(149)(150)(151)(152)(153)(154). "Mainly from Table 5.…”
Section: High-residue Congenermentioning
confidence: 99%